Evaluation of geomagnetic relative palaeointensity as a chronostratigraphic tool in the Southern Ocean: refined Plio-/Pleistocene chronology of IODP Site U1533 (Amundsen Sea, West Antarctica) - Hopkins, Becky; Xuan, Chuang; Hillenbrand, Claus-Dieter; van Peer, Tim E.; Jin, Yuxi; Frederichs, Thomas; Gao, Liang; Bohaty, Steven M. (Quaternary science reviews, 2024)
International Ocean Discovery Program (IODP) Expedition 379 to the Amundsen Sea margin of West Antarctica recovered drill cores at two sites spanning the Latest Miocene-Holocene interval with the aim of reconstructing past West Antarctic Ice Sheet dynamics. The recovered Plio-/Pleistocene sediment sequences offer an opportunity to apply and test different dating approaches in an Antarctic deep-sea drift setting, where the records are nearly continuous and unaffected by scouring of icebergs or grounded ice. Here, through palaeomagnetic analysis of continuous u-channel samples and application of X-ray fluorescence (XRF) scanning, we revise the IODP Exp. 379 Site U1533 age model for the uppermost Pliocene and Pleistocene composite interval (0.0-2.9 Ma). We first refine the magnetostratigraphic age model with high-resolution u-channel analysis and interpreted directional data. Consistent with shipboard results, all major geomagnetic polarity chrons and subchrons are identified in the Pleistocene section. The new high-resolution u-channel dataset also allows us to identify a geomagnetic polarity excursion at ∼884 ka (interpreted as the Kamikatsura excursion) and another excursion at ∼2734 ka with confidence (potentially the Porcupine excursion). Based on the improved polarity stratigraphy, we then develop two new highly resolved age models for Site U1533 using: (i) barium enrichment cycles identified in XRF scanning data, and (ii) geomagnetic relative palaeointensity (RPI). In our first age model, we correlate cyclic variations in sedimentary barium enrichment, inferred to represent changes in export productivity, to glacial‒interglacial cycles of the Lisiecki and Raymo (2005) benthic foraminiferal oxygen isotope (δ18O) stack (LR04). Nearly all Pleistocene Marine Isotope Stages (MIS) are interpreted to be present in the barium enrichment record of Site U1533, assuming simultaneous changes in Antarctic sea-ice extent/local export productivity and global oxygen isotope stratigraphy. We then construct the second, independent age model using the Plio-/Pleistocene RPI record developed for Site U1533, which represents the longest (nearly) continuous RPI record currently available for the Antarctic margin. Comparison of the two, independently derived age models shows a variable offset, on average ± 12 kyr, with the RPI-based ages consistently older than the barium-based ages in the interval from 1.9 to 2.9 Ma and then consistently younger from 0.0 to 1.9 Ma. We interpret these offsets to result from a combination of lock-in depth effects in the younger interval (due to the relatively low sedimentation rates at this site, ∼2 cm/kyr), temporal offsets between global δ18O changes in the deep ocean and productivity response on the Antarctic margin, and/or systematic miscorrelation in the construction of the two age models. Finally, we construct a hybrid age model for the Pleistocene section of Site U1533 by combining a mixture of RPI- and barium-based age tie points that are deemed to be robust. The Site U1533 RPI record is then used, together with other Southern Ocean RPI records, to construct an Antarctic RPI stack (designated as ‘ANT-1600’) for the interval 0.0-1.6 Ma. Although sedimentation rates at two-thirds of the sites selected for the stack are lower than 10 cm/kyr, the new ANT-1600 stack is strongly coherent with the SINT-2000 RPI stack (Valet et al., 2005) on time scales of ∼20-200 kyr, allowing for its use as a regional RPI reference curve in future studies. Overall, we demonstrate that RPI at Antarctic margin/Southern Ocean sites provides a viable and valuable independent dating method for application to Plio-/Pleistocene Antarctic sediments.
Online verfügbar: 1. Januar 2024
Gesehen am 25.06.2024